New records of the family Dascillidae (Coleoptera) from China - Jin, Zhenyu; Qin, Zhao; Ślipiński, Adam (Zootaxa, 2018)
New geographical records for 13 species of Dascillidae in China are provided, of which two, Dascillus vittatus (Pic, 1914) and D. russus Jin et al., 2013 are new Country records. In addition, we provide 10 new province records for 13 species of Chinese Dascillidae. The Yunnan Province holds the richest generic and species diversity of Dascillinae (3 genera, 20 species). A total of 32 species (74%) are Chinese endemics and Yunnan is also found to be the area with the highest endemicity (13 species).